Progressive Compromise of Nouns and Action Verbs in Posterior Cortical Atrophy - Steeb, Brenda; García-Cordero, Indira; Huizing, Marjolein C.; Collazo, Lucas; Borovinsky, Geraldine; Ferrari, Jesica; Cuitiño, Macarena M.; Ibáñez, Agustín; Sedeño, Lucas; García, Adolfo M. (Frontiers in Psychology, 2018)
Processing of nouns and action verbs can be differentially compromised following lesions to posterior and anterior/motor brain regions, respectively. However, little is known about how these deficits progress in the course of neurodegeneration. To address this issue, we assessed productive lexical skills in a patient with posterior cortical atrophy at two different stages of his pathology. On both occasions, he underwent a structural brain imaging protocol and completed semantic fluency tasks requiring retrieval of animals (nouns) and actions (verbs). Imaging results were compared with those of controls via voxel-based morphometry, whereas fluency performance was compared to age-matched norms through Crawford’s t-tests. In the first assessment, the patient exhibited atrophy of more posterior regions supporting multimodal semantics (medial temporal and lingual gyri), together with a selective deficit in noun fluency. Then, by the second assessment, the patient’s atrophy had progressed mainly towards fronto-motor regions (rolandic operculum, inferior and superior frontal gyri) and subcortical motor hubs (cerebellum, thalamus), and his fluency impairments had extended to action verbs. These results offer unprecedented evidence of the specificity of the pathways related to noun and action-verb impairments in the course of neurodegeneration, highlighting the latter’s critical dependence on damage to regions supporting motor functions, as opposed to multimodal semantic processes.